Police sexual misconduct: A national scale study of arrested officers - Brewer, Steven L (2014)
Police sexual misconduct is often considered a hidden crime that routinely goes unreported. The current study provides an empirical data on cases of sex-related police crime at law enforcement agencies across the United States. The study identifies and describes incidents where sworn law enforcement officers were arrested for one or more sex-related crimes through a quantitative content analysis of published newspaper articles and court records. The primary news information source was the Google News search engine using 48 automated Google Alerts. Data are analyzed on 548 arrest cases in the years 2005-2007 of 398 officers employed by 328 nonfederal law enforcement agencies located in 265 counties and independent cities in 43 states and the District of Columbia. Findings indicate that police sexual misconduct includes serious forms of sex-related crime and that victims of sex-related police crime are typically younger than 18 years of age